Cancer anorexia-cachexia syndrome - S Ruengdit (Journal of Health Science and Medical Research (JHSMR), 2009)
Nutrition status is an important factor in treatment result in patients who are suffering from cancer. Nowadays we understand that cancer anorexia-cachexia syndrome is not only from poor appetite or inappropriate nutrition intake but also from chemical substances produced from a tumor or a physical reaction or inflammatory response which alters normal body metabolism. Such reactions are referred to as paraneoplastic syndrome, and there have been recent advances in their treatment, based on the patho- physiology of the disease. A number of clinical trials aiming to improve this condition resulted in improvements in the outcomes of cancer treatments and focused on both medications and dietary modifications.